A comparison between lumped parameter method and computational fluid dynamics method for steady and transient optical-thermal characteristics of the molten salt receiver in solar power tower. (15th April 2022) - Wang, Wen-Qi; Li, Ming-Jia; Jiang, Rui; Cheng, Ze-Dong; He, Ya-Ling
Abstract: Lumped parameter method (LPM), which neglects the change of the temperature within the cross-section of the molten salt, is widely used to predict solar receiver's steady and transient optical-thermal characteristics. To consider the influences of the temperature variation inside molten salts on the performance of solar receivers, the receiver's steady and transient thermal performance are comparatively studied by computational fluid dynamics method (CFD) and LPM. The results show that the rise time of the outlet temperature predicted by the CFD model under the start process, the change of mass flow rate, and the change of direct normal irradiance are more than two times those of the LPM model. Take the start process on spring equinox as an example, the rise time predicted by the CFD and LPM model are 52s and 22s, respectively. Therefore, the temperature distribution within the molten salt should be considered for predicting a more precise transient thermal performance of the receiver. The predicted outlet temperatures in the steady state by the two models are nearly the same, with an absolute difference less than 2.0 °C, which indicates that whether considering the temperature distribution within the molten salt does not influence receiver's steady thermal characteristics. Highlights: LPM and CFD models are used to study reciever's steady and transient performance. CFD model predicts rise time of the outlet temperature twice that of the LPM model. Differences between predicted steady outlet temperatures are less than 2.0 °C. Steady performance of the receiver is not affected by salt's internal temperature. Transient performance is significantly affected by salt's internal temperature.